Drivers of work engagement among managers in Malaysia manufacturing industry - Lee, Yen Shean; Lim, Seng Hian; Ngeow, Pei Hsin; Praveena, Selvalingam; Yow, Mei Yi (2019)
Throughout this whole research, this study investigates on how job autonomy, personal resources and perceived organization support will affect the work engagement of the managers in the manufacturing industry in Malaysia. One of the main purposes of this research is to identify the variables that will affect the working engagement of the managers in the manufacturing industry. This research carried out to recognize which of the independent variables (Job Autonomy, Personal Resources and Perceived Organizational Resources) will affect most to the dependent variable (Work Engagement). The specific objective of the research is to identify whether there is a significant relationship between job autonomy, personal resources, perceived organizational support towards the work engagement of managers. In this research, 400 sets of questionnaire prepared and distributed to the target respondents who are working in manufacturing industries. After the data collected, Statistical Analysis System Enterprise 7.1 (SAS) was used to test the data in order to generate the result. The finding of this research shows that independent variables are positive associated with dependent variable. Through the reliability test, Pearson Correlation Coefficient and Multiple Linear Regression has used to determine the relationship between the IVs and DV.